CAN ONLINE GAMES MOTIVATE STUDENTS' LEARNING? (STUDY ON ELEMENTARY SCHOOL STUDENTS) - Basri, B; Suleman, Asharif; Idayanti, Zulfi (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This research aims to analyze the impact of using online games on SD 2 Kendari students. This type of research is quantitative, and data collection is done through a questionnaire designed to measure the impact of using online games on student learning motivation. The population in the study was 150 students in classes IV and V, and we used purposive sampling techniques. The results of the research show that the level of online game use among SD 2 Kendari students reached 53%. Meanwhile, students' learning motivation is in the medium category, with a percentage of 57%. Meanwhile, the results of hypothesis testing show a significant negative influence between the level of online game use and learning motivation, with a probability value of 0.00 <0.05 and T-count (-4.263) > T-table (2.010), with a contribution of online games to learning motivation of 27.1%. Therefore, this research shows that the level of online game use almost has the same value for learning motivation. Thus, the importance of increasing elementary school students' learning motivation is integral. The use of online games is basically able to motivate, but it still needs to be controlled and accommodate more study hours. Research provides an important understanding that the use of online games must be controlled more consistently so that students study more hours and use online games less.